Advanced abdominal ectopic pregnancy and the role of antenatal ultrasound scan in its diagnosis and management - Byamukama, Anacret; Bibangambah, Prossy; Rwebazibwa, Joseph; Acan, Moses; Sebikali, Mugisha Julius (Radiology Case Reports, 2023)
Abdominal pregnancy is a very rare form of ectopic gestation in which implantation occurs in the peritoneal cavity. It accounts for about 1% of all ectopic pregnancies and is associated with a higher risk of morbidity and mortality due to complications such as preeclampsia, placenta abruption, and oligohydromnios, which necessitate pregnancy termination before term, and the risk of massive hemorrhage associated with abnormal placentation. We present a case of advanced abdominal ectopic pregnancy, diagnosed in the second trimester and complicated by anhydramnios. An abdominal ultrasound scan showed a nongravid uterus and a single live extrauterine fetus within the abdominal cavity, with no sur- rounding liquor at 23 weeks and 3 days’ average gestational age. Mother was consented and an emergency laparatomy performed. A premature baby was delivered but died in Neonatal Intensive Care Unit (NICU) after 4 hours due to severe acute respiratory distress syndrome. Mother had good postoperative recovery. Advanced abdominal ectopic pregnancy though very rare, is associated with complications that lead to early termination. Ultrasound scan is a reliable tool for the diagnosis of abdominal pregnancy in settings with limited access to Magnetic Resonance Imaging (MRI). It should be recommended to all mothers at their earliest antenatal care (ANC) visit to help determine the site of pregnancy and guide further intervention.
Keywords: Ectopic pregnancy; Abdominal pregnancy; Extrauterine pregnancy